Malliavin Calculus for Functionals with Generalized Derivatives and Some Applications to Stable Processes - Kulik, O.M. (Український математичний журнал, 2002)
We introduce the notion of a generalized derivative of a functional on a probability space with respect to some formal differentiation. We establish a sufficient condition for the existence of the distribution density of a functional in terms of its generalized derivative. This result is used for the proof of the smoothness of the distribution of the local time of a stable process. Введено поняття узагальненої похідної функціонала на ймовірнісному просторі відносно формального диференціювання. Отримано достатню умову існування щільності розподілу функціонала у термінах йою узагальненої похідної. Ці результати використано для доведення гладкості розподілу локального часу від стійкого процесу.